Prosumerism in the democratic arena: A critical analysis of social media users' role in the production and dissemination of election information in Indonesia - Indira Isni, Lusiana; Rusadi, Udi; Febrayanto, Catur Raharjo (Institute of Computer Science (IOCS), 2024)
The phenomenon of prosumerism on social media plays a crucial role in influencing the dynamics of citizens' political participation, particularly in the upcoming 2024 Indonesian elections. However, this phenomenon also presents challenges related to the spread of disinformation and polarization. This study aims to explore how prosumers produce and disseminate political content on social media and its impact on public discourse. It posits that prosumerism, through digital platforms, has transformed political participation into a more interactive process, yet remains susceptible to misuse. The theoretical framework includes prosumerism, echo chambers, and digital literacy. A qualitative methodology is employed, utilizing a literature review of various relevant recent studies. The analysis indicates that while prosumerism enhances political participation, it is often trapped within echo chambers that exacerbate biases and the dissemination of disinformation. The conclusion of this research suggests that although prosumerism can broaden political participation, without effective regulation and improvement of digital literacy, it may deepen social polarization and threaten the integrity of democracy.